WORK LIFE BALANCE AS MEDIATOR BETWEEN FINANCIAL WELL-BEING AND TURNOVER INTENTION: MODERATED BY WORK SECTOR OF EMPLOYEES IN CENTRAL LUZON, PHILIPPINES - Ponio, Juris C. (PEOPLE: International Journal of Social Sciences, 2024)
The mediating role of work life balance on the relationship between financial well-being and turnover intention was investigated in this study. Moreover, the possible moderation of work sector was explored. The respondents include the millennial workforce from private and public organizations in Central Luzon, Philippines. The research utilized quantitative approach to assess the relationships between the variables. To quantify the responses, adopted instrument was used and distributed to respondents. The respondents were chosen using purposive sampling design. Data gathered were treated using Partial least square – structural equation modelling (PLS-SEM) through WarpPls 8.0 software. The findings revealed that significant effects were observed on the following: financial well-being on work life balance; work life balance on turnover intention; and financial well-being on turnover intention. Moreover, work life balance was found to partially mediate between financial well-being and turnover intention. However, the moderating effect of work sector on the relationships of the variables was found to be not statistically significant. Given the finding of the study, conclusions were drawn and recommendations were provided to address the issues.